Cereal Grains : Properties, Processing, and Nutritional Attributes. - Serna-Saldivar, Sergio O. (Food preservation technology series., 2010)
Cereal Grains: The Staff of LifeIntroductionCereal Production Versus Population GrowthGeneral CharacteristicsAdaptation and Cytogenetic OriginGeneral UsesNutritional ValueBiotechnologyFuture OutlookPhysical Properties, Grading, and Specialty GrainsIntroductionPhysical Properties of Cereal GrainsGrain QualityClassification and Grading SystemsSpecialty CerealsChemical Composition of Cereal GrainsIntroductionProximate CompositionCarbohydratesProteinsLipidsMinerals and VitaminsGrain Development, Morphology, and StructureIntroductionPollination, Fertilization, And Grain DevelopmentMorphology And St.